The Phenomenon of Academic Burnout in Students: A Literature Study - Andini Dwi Arumsari; Maheswari Ayu Pratiwi; Muhammad Iqbal Ramadhan; Khoirun Nisa; Ghina Ibra Syakira (P3I UMSurabaya, 2025)
The phenomenon of academic burnout among university students has become an increasingly significant issue in modern higher education. This paper presents a literature review of 20 scholarly articles, both national and international, published between 2015 and 2024. The findings indicate that academic burnout is characterized by emotional exhaustion, depersonalization, and reduced academic achievement resulting from prolonged academic pressure. Contributing factors include individual aspects (low motivation, poor self-regulation, and maladaptive coping), social factors (lack of support from peers, family, and lecturers), and institutional factors (excessive academic workload and rigid evaluation systems). Conversely, protective factors such as academic resilience, self-efficacy, social support, and mindfulness practices can mitigate burnout risks. Academic burnout negatively affects students’ academic performance and mental health, leading to increased anxiety and depression. Therefore, university-based interventions that promote a balance between academic demands and students’ psychological well-being are essential.